Pharmacological and biotransformation studies of 1-acyl-substituted derivatives of d-lysergic acid diethylamide (LSD). (1st August 2020) - Halberstadt, Adam L.; Chatha, Muhammad; Klein, Adam K.; McCorvy, John D.; Meyer, Markus R.; Wagmann, Lea; Stratford, Alexander; Brandt, Simon D.
Abstract: The ergoline d -lysergic acid diethylamide (LSD) is one of the most potent psychedelic drugs. 1-Acetyl-LSD (ALD-52), a derivative of LSD containing an acetyl group on the indole nitrogen, also produces psychedelic effects in humans and has about the same potency as LSD. Recently, several other 1-acyl-substitued LSD derivatives, including 1-propanoyl-LSD (1P-LSD) and 1-butanoyl-LSD (1B-LSD), have appeared as designer drugs. Although these compounds are assumed to act as prodrugs for LSD, studies have not specifically tested this prediction. The present investigation was conducted to address the gap of information about the pharmacological effects and mechanism-of-action of 1-acyl-substituted LSD derivatives. Competitive binding studies and calcium mobilization assays were performed to assess the interaction of ALD-52, 1P-LSD, and 1B-LSD with serotonin 5-HT2 receptor subtypes. A receptorome screening was performed with 1B-LSD to assess its binding to other potential targets. Head twitch response (HTR) studies were performed in C57BL/6J mice to assess in vivo activation of 5-HT2A (the receptor thought to be primarily responsible for hallucinogenesis). Finally, liquid chromatography/ion-trap mass spectrometry (LC/MS) was used to quantify plasma levels of LSD in Sprague-Dawley rats treated with ALD-52 and 1P-LSD. 1-Acyl-substitution reduced the affinity of LSD for most monoamine receptors, including 5-HT2A sites, by one to two orders of magnitude. Although LSD acts as an agonist at 5-HT2 subtypes, ALD-52, 1P-LSD and 1B-LSD have weak efficacy or act as antagonists in Ca 2+ -mobilization assays. Despite the detrimental effect of 1-acyl substitution on 5-HT2A affinity and efficacy, 1-acyl-substitued LSD derivatives induce head twitches in mice with relatively high potency. High levels of LSD were detected in the plasma of rats after subcutaneous administration of ALD-52 and 1P-LSD, demonstrating these compounds are rapidly and efficiently deacylated in vivo . These findings are consistent with the prediction that ALD-52, 1P-LSD and 1B-LSD serve as prodrugs for LSD. This article is part of the special issue entitled 'Serotonin Research: Crossing Scales and Boundaries'. Highlights: N 1 -Substituted LSD derivatives such as ALD-52 are potent hallucinogens in humans. N 1 -Substitution markedly reduces the efficacy of LSD at the 5-HT2A receptor. ALD-52 and 1P-LSD are metabolized to LSD in rats. N 1 -Substituted LSD derivatives likely act as prodrugs.